2014
DOI: 10.1007/s12282-014-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative courses of breast reconstruction using inferior adipofascial tissue repair

Abstract: All patients with IATR were treated with irradiation, and no image findings of a partial or total necrosis of the flap recognized 1 year after examination. They produced good cosmetic results; however, they could not elevate the QOL score on the whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…As it covers all cancers, QOL-ACD-B as a breast cancer disease-specific scale is available (Otsuka et al 2015) (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…As it covers all cancers, QOL-ACD-B as a breast cancer disease-specific scale is available (Otsuka et al 2015) (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Six studies were considered eligible and were included in this systematic review . From the six studies identified, five were retrospective case–control studies and one was a prospective cohort study (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Half of the identified studies were conducted in the UK. The remaining three studies were conducted in several other different geographic contexts . All six studies were single‐institution studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty five months of mean followup showed satisfactory cosmetic results. Otsuka et al [18] performed inframammary adipofascial tissue repair (IATR) on 25 patients with breast cancer in inferior site. They used a tongue shaped flap to repair the defect.…”
Section: Discussionmentioning
confidence: 99%